The Male Athlete Triad - A consensus statement from the female and male athlete triad coalition part 2: Diagnosis, treatment, and return-to-play - Fredericson, M.; Kussman, A.; Misra, M.; Barrack, M. T.; De Souza, M. J.; Kraus, E.; Koltun, K. J.; Williams, N. I.; Joy, E.; Nattiv, A. (Clinical Journal of Sport Medicine, 2021)
The Male Athlete Triad is a medical syndrome most common in adolescent and young adult male athletes in sports that emphasize a lean physique, especially endurance and weight-class athletes. The 3 interrelated conditions of the Male Athlete Triad occur on spectrums of energy deficiency/low energy availability (EA), suppression of the hypothalamic-pituitary-gonadal axis, and impaired bone health, ranging from optimal health to clinically relevant outcomes of energy deficiency/low EA with or without disordered eating or eating disorder, functional hypogonadotropic hypogonadism, and osteoporosis or low bone mineral density with or without bone stress injury (BSI). Because of the importance of bone mass acquisition and health concerns in adolescence, screening is recommended during this time period in the at-risk male athlete. Diagnosis of the Male Athlete Triad is best accomplished by a multidisciplinary medical team. Clearance and return-to-play guidelines are recommended to optimize prevention and treatment. Evidence-based risk assessment protocols for the male athlete at risk for the Male Athlete Triad have been shown to be predictive for BSI and impaired bone health and should be encouraged. Improving energetic status through optimal fueling is the mainstay of treatment. A Roundtable on the Male Athlete Triad was convened by the Female and Male Athlete Triad Coalition in conjunction with the 64th Annual Meeting of the American College of Sports Medicine in Denver, Colorado, in May of 2017. In this second article, the latest clinical research to support current models of screening, diagnosis, and management for at-risk male athlete is reviewed with evidence-based recommendations.